Four-boson scale near a Feshbach resonance - Yamashita, Marcelo Takeshi [UNESP]; Tomio, Lauro; Delfino, A.; Frederico, T. (Edp Sciences S A, 2006)
We show that an independent four-body momentum scale mu((4)) drives the tetramer binding energy for fixed trimer energy (or three-body scale mu((3))) and large scattering length (a). The three- and four-body forces from the one-channel reduction of the atomic interaction near a Feshbach resonance disentangle mu((4)) and mu((3)). The four-body independent scale is also manifested through a family of Tjon lines, with slope given by mu((4))/mu((3)) for a(-1) = 0. There is the possibility of a new renormalization group limit cycle due to the new scale.